2020
DOI: 10.1001/jamanetworkopen.2020.19039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Low-Dose Computed Tomography Lung Cancer Screening Program in Henan, China

Abstract: IMPORTANCE Lung cancer screening has been widely implemented in Europe and the US. However, there is little evidence on participation and diagnostic yields in population-based lung cancer screening in China. OBJECTIVE To assess the participation rate and detection rate of lung cancer in a population-based screening program and the factors associated with participation. DESIGN, SETTING, AND PARTICIPANTS This cross-sectional study used data from the Cancer Screening Program in Urban China from October 2013 to Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
0
30
2
Order By: Relevance
“…Therefore, in the present study, with the focus on established risk factors for lung cancer routinely available in general cancer screening settings, we aimed to develop and internally validated a risk prediction model for lung cancer. The details of the CanSPUC could be found in previously published articles [48]. Briefly, after obtaining signed written informed consent, all the participants completed a questionnaire that included demographic characteristics, lifestyle factors, items assessing general health and medical history, and family history of common disease.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, with the focus on established risk factors for lung cancer routinely available in general cancer screening settings, we aimed to develop and internally validated a risk prediction model for lung cancer. The details of the CanSPUC could be found in previously published articles [48]. Briefly, after obtaining signed written informed consent, all the participants completed a questionnaire that included demographic characteristics, lifestyle factors, items assessing general health and medical history, and family history of common disease.…”
Section: Introductionmentioning
confidence: 99%
“…The model was developed based on the Cancer Screening Program in Urban China (CanSPUC) ( 45 ). With the focus on established risk factors for lung cancer routinely available in general cancer screening settings, we aimed to develop and internally validated a risk prediction model for lung cancer in Chinese non-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important observation since women may show a higher adherence to LCS, allegedly related to their decennial experience with breast cancer screening. The above-mentioned CanSPUC study showed 50 % adherence among women, compared to a significantly lower rate of 33 % among men [30].…”
Section: Introductionmentioning
confidence: 85%
“…Several factors were associated with the lower participation rate, including age range 70-74 years, male gender, lower education level, no family history of LC, and current smoking status. Furthermore, the participation rate was heterogeneous between different regions, which can be related to a longer distance to the screening site [30]. To overcome such a limitation, the Manchester Lung Health Check program (a pilot community-based study) used mobile CT scanners placed outside shopping centers, with the purpose of providing access to LCS for high-risk subjects from the most deprived areas of Manchester [31].…”
Section: Introductionmentioning
confidence: 99%